The age of productivity : transforming economies from the bottom up - Pages, Carmen (Development in the Americas, 2010)
Productivity, the main driver of economic prosperity, is languishing in Latin America and the Caribbean and is preventing the region from catching up with the developed world. Asking why the region is falling farther and farther behind, this book looks beyond the traditional macro explanations and digs all the way down to the industry and firm level to uncover the causes of this low productivity. It provides tools to ponder productivity growth beyond conventional aggregate analysis, focusing on the extreme heterogeneity of sectors and firms while emphasizing the importance of policies that allow high productivity firms to thrive and expand. While it certainly considers the plight of manufacturing, the book zeros in on the critical services sectors, particularly those, such as transportation and retail, with important repercussions on the rest of the economy. It challenges the argument that the region is condemned to stagnation and examines a number of policy levers that can transform the economies of the region.--Publisher's description